2021
DOI: 10.1111/acps.13335
|View full text |Cite
|
Sign up to set email alerts
|

The effects of psychotherapies for depression on response, remission, reliable change, and deterioration: A meta‐analysis

Abstract: Objective Meta‐analyses of psychotherapies usually report effects sizes, while clinicians and patients need to know the proportion of patients who benefit from therapy. We conducted a meta‐analysis of therapies for depression reporting the rates of response (50% symptom reduction), remission (HAM‐D <7), clinical significant deterioration for psychotherapy, and control conditions (CAU, waitlist, and pill placebo), as well as the relative risk of these outcomes and the numbers‐needed‐to‐be‐treated (NNTs). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(133 citation statements)
references
References 31 publications
6
122
1
4
Order By: Relevance
“…Study III indicated that this number was up to 60 % two years after the conclusion of the first RCT. The percentage of reliably improved respondents in Study IV is lower than the roughly 60 % found in a meta-analysis of the effects of psychotherapeutic interventions on depression by Cuijpers et al (2021). It is worth mentioning that the calculation of reliable clinical change made use of the one-year testretest coefficient for the ULS-3 (0.73) which is rather low.…”
Section: Icbt Can Be a Helpful Tool For Reducing Loneliness…mentioning
confidence: 62%
“…Study III indicated that this number was up to 60 % two years after the conclusion of the first RCT. The percentage of reliably improved respondents in Study IV is lower than the roughly 60 % found in a meta-analysis of the effects of psychotherapeutic interventions on depression by Cuijpers et al (2021). It is worth mentioning that the calculation of reliable clinical change made use of the one-year testretest coefficient for the ULS-3 (0.73) which is rather low.…”
Section: Icbt Can Be a Helpful Tool For Reducing Loneliness…mentioning
confidence: 62%
“…However, this does not necessarily have to be the result of the treatment but may be related to other causes ( Dimidjian and Hollon, 2010 ), illustrating the importance to compare these rates with those in control conditions. The results of a recent meta-analysis on the effects of psychotherapy for depression indicate that deterioration rates are below 5% in the treatment condition and between 7% and 13% in control conditions (care-as-usual, waitlist, or pill placebo; Cuijpers et al, 2021 ). Being aware of various definitions existing in the literature today, the current article uses the term negative effect as a description of every possible event a participant might encounter during the course of treatment that is experienced as negative and perceived as related to the treatment by the participant.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…According to the most recent meta-analysis, only approximately 5% of patients deteriorate while in psychotherapeutic treatment [3]. Adverse Events (AE; e.g.…”
Section: Safety/harmsmentioning
confidence: 99%
“…This has led to the development of several disorderspecific approaches such as the Cognitive Behavioural Therapy (CBT) [1] and the Interpersonal Psychotherapy (IPT) [2]. While these approaches (among others) have proven efficacy in unipolar major depression, there is a large proportion of patients who do not respond (more than 50%) or do not reach full remission (about two thirds) with first line treatment [3], even when the procedure is in accordance with treatment guidelines [4,5]. Major reasons for individual non-response and non-remission include interindividual heterogeneity of etiological mechanisms of depression and high rates of comorbid disorders of up to 80% in clinical and epidemiological studies [6][7][8].…”
Section: Introductionmentioning
confidence: 99%